The approximation of the functions from the classes by Steklov’s operators - Репета, В.К.; Репета, Л.А. (Proceedings of National Aviation University (archive), 2004)
The behavior of the upper bounds of the deviations of the -varied functions of Steklov’s operators, which are the particular case of the operators of the form in the integral metric, was investigated using the integral representation of those deviations from the linear operators.